THE FACTORS RELATED TO EVENTS LUNG TUBERCULOSIS IN THE WORKING AREA OF PUSKESMAS BANDAR KHALIFAH TEMBUNG - Tengku Khairunnisa; Mesi Valia Delanova; Mafe Robbi Simanjuntak; Pahala Maringa J Simangunsong; Masryna Siagian (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
TB is the ninth leading cause of death worldwide and the leading cause of an infectious agent, ranking above HIV / AIDS. an estimated 1.3 million deaths (World Health Organization, 2017). The results of the latest data survey conducted on July 28, 2020, data that we obtained from P2 Pulmonary Tuberculosis Puskesmas Bandar Khalifah Tembung, there were 107 patients who were male as many as 67 and female as many as 40 patients. The number of patients with confirmed bacteriology / AFB (+) was 69 patients, and the number of patients with clinical confirmation / AFB (-) was 38 patients (Puskesmas Bandar Khalifah, 2020). The population in this study were 107 patients with pulmonary tuberculosis in the Bandar Khalifah Tembung Community Health Center from January to July 2020. The sampling technique used in this study was total sampling, where the sample was taken covering the entire population of 107 people. Based on statistical tests using the chi-square test, there was a relationship of knowledge with the incidence of pulmonary tuberculosis with a value (p = 0.025), there was no relationship between occupancy density and the incidence of pulmonary tuberculosis with a value (p = 0.547), there was no relationship with household contact with the incidence of pulmonary tuberculosis with value (p = 0.241) and there is a relationship between smoking habits and the incidence of pulmonary tuberculosis with a value (p = 0.045). The conclusion of this study is that there is a relationship between knowledge and smoking habits in the work area of the Bandar Khalifah Public Health Center. It is hoped that the Bandar Khalifah Community Health Center will be more active in fostering and carrying out program activities on Tuberculosis for the community and sufferers.